Applying the principles of adaptive leadership to person‐centred care for people with complex care needs: Considerations for care providers, patients, caregivers and organizations - Kerry Kuluski; Robert J. Reid; G. Ross Baker (Wiley, 2021)
Abstract Background Health systems in many countries see person‐centred care as a critical component of high‐quality care but many struggle to operationalize it in practice. We argue that models such as adaptive leadership can be a critical lever to support person‐centred care, particularly for people who have multiple complex care needs. Objective To reflect on two concepts: person‐centred care and adaptive leadership and share how adaptive leadership can advance person‐centred care at the front‐line care delivery level and the organizational level. Findings The defining feature of adaptive leadership is the separation of technical solutions (ie applying existing knowledge and techniques to problems) from adaptive solutions (ie requiring shifts in how people work together, not just what they do). Addressing adaptive challenges requires identifying key assumptions that may limit motivations for change and the behaviours influenced by these assumptions. Thus, effective care for patients, particularly those with multiple complex care needs, often entails helping care providers and patients to examine their relationships and behaviours not just identifying technical solutions. Addressing adaptive challenges also requires a supportive and enabling organizational context. We provide illustrative examples of how adaptive leadership principles can be applied at both the front line of care and the organization level in advancing person‐centred care delivery. Conclusions Advancing person‐centred care at both the clinical and organizational levels requires a growth mindset, a willingness to try (and fail) and try again, comfort in being uncomfortable and a commitment to figure things out, in partnership, in iterative ways. Patients, caregivers, care providers and organizational leaders all need to be adaptive leaders in this endeavour.